2004
DOI: 10.1038/sj.jhh.1001720
|View full text |Cite
|
Sign up to set email alerts
|

Is inappropriate left ventricular mass related to neurohormonal factors and/or arterial changes in hypertension? a LIFE substudy

Abstract: We investigated whether inappropriately high left ventricular (LV) mass, defined as observed LV mass exceeding the level of individual LV mass predicted from gender, height, and stroke work, may be associated with an imbalance between growth-promoting and growth-inhibitory factors and/or structural vascular changes. In 53 patients with hypertension and electrocardiographic LV hypertrophy, 24-h ambulatory blood pressure (BP); echocardiographic LV mass, stroke volume and stroke work; minimal forearm vascular res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
4
1
1
Order By: Relevance
“…The results of studies that evaluated the associations of ET-1 with LVM i are not consistent. While a few small studies (n <60) reported a significant association of plasma CT-proET-1 with LVM i ,24,25,27 other studies (n =50-120) found no significant association 28-30. In our study, plasma CT-proET-1 was associated with LVM i after adjustment for adjustment for conventional cardiovascular risk factors and medication use ( P =0.002).…”
Section: Discussioncontrasting
confidence: 57%
“…The results of studies that evaluated the associations of ET-1 with LVM i are not consistent. While a few small studies (n <60) reported a significant association of plasma CT-proET-1 with LVM i ,24,25,27 other studies (n =50-120) found no significant association 28-30. In our study, plasma CT-proET-1 was associated with LVM i after adjustment for adjustment for conventional cardiovascular risk factors and medication use ( P =0.002).…”
Section: Discussioncontrasting
confidence: 57%
“…Notably, the prevalence of iLVM we found in our RA patients was more than two-fold higher than that detected in the settings of patients mentioned above, suggesting RA disease a specific condition by which LVM is inappropriately produced together with myocardial fibrosis. The biochemical processes leading to iLVM are not known: iLVM was not significantly related to arterial changes or to any circulating growth factor traditionally measured in patients with arterial hypertension [35]. However, what we can gather from our finding is that a worrisome condition named iLVM can be easily detected by standard echocardiography at an early stage of RA disease, when the changes in cardiovascular geometry and systolic function are already evident [36][37][38][39].…”
Section: Discussionmentioning
confidence: 71%
“…Conversely, the prevalence of inappropriate LV mass was particularly high in the subgroups of patients with LV hypertrophy, and this behaviour was detected more frequently in patients with AH than aortic stenosis. It is possible that the role of nonhaemodynamic factors as determinants of LV mass inappropriateness such as proto-oncogenes and other growth factors, cytokines, plasma noradrenaline and other neurohormones has more influence in AH than aortic stenosis patients [33][34][35]. Recent studies documented a significant increase in a member of the interleukin-6 superfamily, 'cardiotrophin-1', in patients with inappropriate LV mass.…”
Section: Discussionmentioning
confidence: 96%